Primary teacher backgrounds and ESD competencies: An exploratory study - Dadi Mulyadi; Ridha Hidayani; Lucia Ekawati Ikanubun (Education and Development Research, 2026)
Education for Sustainable Development (ESD) emphasizes the crucial role of teachers in cultivating students' sustainability competencies. However, studies on how teachers’ background characteristics relate to their ESD competencies remain limited, particularly at the primary school level. This study examined whether widely assumed demographic and administrative differences among teachers including gender, years of teaching experience, and employment status are associated with their ESD competence. A quantitative correlational design was employed using the Chi-Square test to analyze the association between gender and competence, and the Kruskal-Wallis test to assess the relationship between teaching experience and employment status to examine group-based differences and associations among demographic variables. The findings indicate no statistically significant differences across all variables. Gender was not associated with teachers’ ESD competence (p = 0.102), and competence levels did not differ significantly by teaching duration (p = 0.740) or employment status (p = 0.443). These results suggest that demographic and administrative characteristics are not decisive in shaping teachers’ ESD competencies, providing a broadly inclusive teacher training and curriculum initiatives. The study contributes to the conceptual insights for framing inclusive ESD primary teacher competencies. This implies that strengthening ESD implementation at the primary level requires sustained training programs, practical teaching materials, and a supportive school culture that empowers teachers to embed sustainability concepts into early learning. Future studies are recommended to investigate systemic and school-level factors such as curriculum design, leadership practices, and community engagement that may better explain variations in ESD competence among primary school teachers.